STRATEGI KOMUNIKASI POLITIK PEMENANGAN JOKOWI-MA'RUF AMIN KEPADA GENERASI MILENIAL DI TANGERANG SELATAN PADA PEMILU 2019. - Fairuz Syarifah (2023)
This study aims to determine Jokowi's political communication strategy in getting millennial vote participation in the 2019 Presidential Election in the South Tangerang region, which is known to be millennial voters in the 2019 Presidential Election to determine victory for each candidate for President and Vice President as well as to be a comparison and basis for evaluation, lessons for the next election. The method used in this research is mixed methods or mix. The type of research used is the exploratory sequential design which is data collection that begins with the collection of qualitative data and then continues with the collection of quantitative data. The sampling technique was carried out by non-probability sampling. Researchers used 3 quantitative data analysis techniques, namely validity test, reliability test and simple linear regression test and then used four stages of qualitative data analysis according to Miles & Huberman, namely data collection, data reduction, data presentation, and conclusion/verification. The form of a political communication strategy for the millennial generation carried out by the Jokowi-Ma'ruf Amin pair with the South Tangerang Regional Campaign Team, namely, political campaigns and mass media. The political communication strategy with political campaigns is by conducting outreach related to political literacy to the millennial generation, holding fashion parades, political messages to fellow millennials, interesting events for millennials such as music concerts, convoys of Jokowi supporters, etc., as well as door to door campaigns. Meanwhile, the mass media political communication strategy used by Jokowi-Ma'ruf Amin with the South Tangerang Regional Campaign Team is by using social media and electronic media and campaign props or print media.